The Creation of National Cultures through Education, the Inequities They Produce, and the Challenges for Multicultural Education - Smagorinsky, Peter (International Journal of Multicultural Education, 2022)
This essay compares and contrasts the educational movements of three nations—the United States, Mexico, and the Soviet Union—established according to Eurocentric cultural values. In each country, mass education was undertaken to help produce an assimilative national culture during formative periods characterized by instability. In two of these nations, the U.S. and Mexico, this foundation eventually required an accommodation to address multiculturalism. This latter-day perspective is designed to recognize, respect, and appreciate a variety of cultures. This essay examines the ways in which these two oppositional goals—monoculturalism and multiculturalism—have intersected in schools.